Pengelolaan Wakaf Uang Pada Lembaga Pusat Pengelolaan Dana Sosial dalam Bidang Pendidikan di Universitas Airlangga Surabaya - Alfian Rico Firmansyah (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
One of the institutions in Islam that has a great contribution and potential to the welfare of Muslims in waqf. Waqf is also a religious practice which is closely related to the welfare of the people. One of the sources of Islamic finance which has the potential to develop the economy of the people is waqf. Even though the potential of waqf in Indonesia is quite large, the management of waqf in Indonesia is still said to be underdeveloped when compared to other countries even though it has such a large contribution. With the potential for land waqf which is very broad, which should have and save a very large economic potential, currently it has not been managed optimally. However, the waqf assets in Indonesia in the form of land in the management and allocation are still allocated for mosques at 44.64%, musholla 28.23%, schools 10.63%, social 8.58% and funerals 4.50%.